Data structures and algorithms made easy in java : data structure and algorithmic puzzles - Karumanchi, Narasimha (India : CareerMonk Publications, 2018)
Introduction.--Recursion and backtracking.--Linked lists.--Stacks.--Queues.--Trees.--Priority queues and Heaps.--Disjoint set ADT.--Graph algorithms.--Sorting.--Searching.--Selection algorithms [Medians].--Symbol tables.--Hashing.--String algorithms.--Algorithms design techniques.--Greedy algorithms.--Divide and conquer algorithms.--Dynamic programming.--Complexity classes.--Miscellaneous concepts.--References.
Originally published in 2015, 435 pages.
Includes bibliographical references.
BBS
Keywords: Data structures (Computer science).; Computer algorithms; Computer programming; Employment interviewing; Computer science